How Women’s Community Shape Social Enterprise and it’s Impact? - Chusnul Rofiah (Jambura Science of Management, 2022)
This paper aims to present how the strength of the women's community is to solve the problems of economic and nutritional adversity through social enterprises established by the women's community. Moreover women are described as motivated not by reasons of money but rather by a desire to act as what can only be described as the mother of the community: women exist to help, to build, for others but never for themselves, and are rarely valued or rewarded for they job. The methods used in data collection are observation, interviews, and photo documentation. The analysis refers to the hermeneutic phenomenological approach by Van Manen (2001), which describes that researchers "mediate" between the meanings of different life experiences. The result of this analysis is the identification of the meaning of success for the women's community through social enterprises. The results of the study indicate that in establishing a women's social enterprise and staying focused on impact, it is necessary to include (1) Women's Leadership Style; (2) Identification with the Community; (3) Participation Process: Listening And Collaborative Atmosphere; (4) Networking. The contribution given from this research is in the fields of economics and business, especially in the strategy of establishing social enterprises for women in the third sector. The implication of this research is the selection of a social business establishment strategy and the focus of solving the problems to be solved.